FUZZY QUERIES IN BLACK-SCHOLES MODEL FOR FINANCIAL OPTIONS - Banasik, Arkadiusz (International Journal of Computing, 2014)
An approach how to use fuzzy queries in field of financial options is described. It provides the key aspect of information for investor expressed in natural language or queries in natural language. Presented paper indicates the first step in knowledge base creation for investor showing how to apply the corresponding mathematical apparatus to cope with natural language statements in Black-Scholes Model for option pricing.